The Effectiveness of the Video Assistant Poblem Based Learning Model to Improve Mathematics Problem Solving Ability and Student Independence in MTs Al Jamiyatul Washliyah Tanjung Morawa Academic Year 2021/2022 - Dwi Maya Sari; Rita Destini (International Journal of Educational Research Excellence (IJERE), 2022)
This study aims to: (1) To find out the video-assisted Problem Based Learning model in improving mathematical problem solving abilities in class VII MTs students. Al-Jamiyatul Washliyah Tanjung Morawa. (2) To find out the effectiveness of the video-assisted Problem Based Learning model in increasing learning independence in class VII MTs students. Al-Jamiyatul Washliyah Tanjung Morawa. This research uses mixed methods (Mixed Methods). This research was conducted in MTs School. Al-Jamiyatul Washliyah Tanjung Morawa with 30 students. The instruments used in this research are mathematical problem solving ability tests, learning independence questionnaires and interviews. The results of this study indicate that: (1) Video-assisted Problem Based Learning model is effective in improving students' mathematical problem solving abilities. (2) Video-assisted Problem Based Learning Model is effective in increasing students' mathematical learning independence.